Making good on donors’ desire to Do Development Differently - Honig, Dan; Gulrajani, Nilima (Third World Quarterly, 2018)
AbstractForeign aid donors are increasingly focused on changing the wa y their development agencies function. This discourse has focused on d esired qualities, including greater knowledge of local contextual real ities, appropriate adaptation to context and greater flexibility to re spond to changing circumstances. We argue that more attention needs to be devoted to the achievement of these qualities and turn to continge ncy theory to identify some under-exploited ways to ?do development di fferently?. The qualities sought by donors are emergent properties of complex organisational systems and will only be achieved through a mic ro-level and interlinked focus on the fundamentals of organisation.